THE HOLOCENE VEGETATION HISTORY OF LAKE ERHAI, YUNNAN PROVINCE SOUTHWESTERN CHINA: THE ROLE OF CLIMATE AND HUMAN FORCINGS - Shen Ji.; Jones R.T.; Yang X.; Dearing J.A.; Wang S. (My University, 2006)
A pollen diagram from a 6.62 m sediment sequence in Lake Erhai in northwest Yunnan, China was obtained to examine the roles of climate change and human impact on the development of the Erhai lake-catchment system since 12950 cal. yr BP. The record extends back into the Younger Dryas, where the dominance of Betula and deciduous Quercus points to a relatively cold and wet winter climate. After 11 750 cal. yr BP, a warming climate coupled with enhanced summer monsoon precipitation results in the expansion of Tsuga and evergreen broadleaved trees (Cyclobalanopsis, Lithocarpus and Castanopsis). An increase in evergreen oaks and dry-tolerant species after 10 320 cal. yr BP suggests a greater seasonality in rainfall, reflecting a southward shift in the winter front across the region. This trend of increasing temperatures and seasonality is seen to continue through into the mid-Holocene and the onset of the Holocene optimum. A marked decline in arboreal taxa coupled with increased levels of grass (Poaceae) and other disturbance taxa provides the first evidence for human impact in the catchment at c. 6370 cal. yr BP. This early phase of forest clearance leads to the collapse of the natural altitudinal vegetation gradient that existed in the catchment from the Lateglacial. The subsequent expansion of secondary pine forest suggests that these early clearances were part of a sustained period of shifting agriculture. Archaeological and historical records for the region point to a gradual increase in immigration into the region throughout the late Holocene. The increased pressure on the catchment is reflected in the pollen record by a series of clearance phases, which increase in intensity after 2140 cal. yr BP, linked presumably to intensification of agriculture and early urbanization. This trend continues through the last millennium, before a sharp increase in arboreal pollen at the top of the core reflects a phase of reforestation that took place in the catchment over the last 25 years.
Keywords: LAKE ERHAI; YUNNAN; HOLOCENE; POLLEN; VEGETATION HISTORY; CLIMATE CHANGE INFLUENCE; HUMAN; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен